Yellow fever vaccination before and during the covid-19 pandemic in Brazil - Tércia Moreira Ribeiro da Silva; Ana Carolina Micheletti Gomide Nogueira de Sá; Elton Junio Sady Prates; Daiana Elias Rodrigues; Thales Philipe Rodrigues da Silva; Fernanda Penido Matozinhos; Ed Wilson Rodrigues Vieira (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To analyze the number of yellow fever vaccine doses administered before and during the covid-19 pandemic in Brazil. METHODS This is an ecological, time series study based on data from the National Immunization Program. Differences between the median number of yellow fever vaccine doses administered in Brazil and in its regions before (from April/2019 to March/2020) and after (from April/2020 to March/2021) the implementation of social distancing measures in the country were assessed via the Mann-Whitney test. Prais-Winsten regression models were used for time series analyses. RESULTS We found a reduction in the median number of yellow fever vaccine doses administered in Brazil and in its regions: North (-34.71%), Midwest (-21.72%), South (-63.50%), and Southeast (-34.42%) (p < 0.05). Series showed stationary behavior in Brazil and in its five regions during the covid-19 pandemic (p > 0.05). Brazilian states also showed stationary trends, except for two states which recorded an increasing trend in the number of administered yellow fever vaccine doses, namely: Alagoas State (before: β = 64, p = 0.081; after: β = 897, p = 0.039), which became a yellow fever vaccine recommendation zone, and Roraima State (before: β = 68, p = 0.724; after: β = 150, p = 0.000), which intensified yellow fever vaccinations due to a yellow fever case confirmation in a Venezuelan State in 2020. CONCLUSION The reduced number of yellow fever vaccine doses administered during the covid-19 pandemic in Brazil may favor the reemergence of urban yellow fever cases in the country.